Pengaruh Kemudahan Pembayaran dan Keamanan Transaksi terhadap Keputusan Pembelian Online - Vanessa Vanessa; Valentino Hugo; Albert Herlambang (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This study is motivated by the rapid growth of online transactions, driven by advances in digital technology, which has led to an increase in the use of digital payment systems in e-commerce. In this context, ease of payment and transaction security are key factors influencing consumers’ purchasing decisions. This study aims to analyse the influence of payment convenience and transaction security on online purchasing decisions. The research method employed is a qualitative approach involving a literature review through the collection of data from various relevant scientific journals. The results indicate that payment convenience influences purchasing decisions because systems that are easy to learn, use, and operate enhance consumer comfort and interest in transacting. Furthermore, transaction security also influences purchasing decisions as it provides assurance of data protection, a sense of security, and consumer confidence when conducting online transactions. However, some studies have shown differing results regarding the influence of these two variables. Overall, payment convenience and transaction security play a significant role in driving online purchasing decisions.